IMPROVEMENT OF COTTON REGENATOR (Conferencea, 2022)
The research in this paper aims to improve machine productivity and cleaning efficiency by improving the cotton regeneration machine after the decontamination process. An improved regenerator was proposed for research and the optimal parameters of the working bodies were determined.